A Comparative Analysis of Organizational Citizenship Behavior, Employee Morale, and Job Performance Across Hierarchical Levels: Exploring Differences in Private and Government Sector Employees - Bhuchar, Vivek; Sukirti, Sukirti; Sharma, Parul (Journal of Neonatal Surgery, 2025)
Organizational Citizenship Behavior (OCB) is a critical element in enhancing employee morale and job performance across varied organizational structures. This paper presents a qualitative, comparative analysis of secondary data from peer-reviewed literature spanning the last five years. The study examines the interplay between OCB, morale, and performance across hierarchical levels within public and private sector organizations. Findings indicate a strong positive correlation among the three constructs. While private sector employees demonstrate higher performance due to incentive-driven environments, they often face lower morale. Conversely, public sector employees benefit from higher morale due to job security but may show moderate performance. The hierarchical level also moderates these relationships, with senior-level employees displaying higher OCB due to greater autonomy and recognition. This paper contributes to organizational behavior literature by emphasizing contextual nuances in applying OCB strategies.